Liver Vitamin A Storage in Fattening Cattle Following Intraruminal of Intramuscular Injection of Vitamin A - Roberts, W. K. (1965)
The effect of intramuscular or intraruminal injection of 1 million I.U. of an emulsifiable vitamin A preparation upon liver vitamin A stores in fattening steers was investigated. Pre-injection liver stores were 52 mcg vitamin A/gm fresh liver. At 7 days post-injection, these stores had increased to an average of 88 mcg vitamin A/gm fresh liver. Thereafter, the liver vitamin A stores declined until at 73 days post-injection they were approximately 28 mcg vitamin A/gm fresh liver. During depletion the pre-injection liver vitamin A levels were reached between 30-35 days post-injection. The method of administration had little effect on repletion of liver vitamin A stores; however, the steers injected intramuscularly showed a slightly slower depletion of liver vitamin A, than those injected intraruminally. Very little difference was observed in average daily weight gains between the two methods of vitamin A administration.